THE EFFECT OF CONVENIENCE AND SECURITY OF USING QRIS PAYMENT METHODS ON PURCHASING DECISIONS WITH TRUST AS AN INTERVENING VARIABLE - RIZKIANI, FITRAH; Bachri, Syamsul; Ponirin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to determine the effect of convenience and security of using digital payment methods (QRIS) on consumer purchasing decisions with trust as an intervening variable (the case of Generation Z purchases in Palu City). The type of research is quantitative. The research sample was Gen Z in Palu City which was determined through purposive sampling method and amounted to 100 people. This study uses the Structural Equation Modeling (SEM) method, which is operated with SMART-PLS. The results of this study indicate that 1) Ease of use of digital payment methods (QRIS) has a significant effect on purchasing decisions, 2) Security of using digital payment methods (QRIS) has a significant effect on purchasing decisions, 3) Ease of use of digital payment methods (QRIS) has a significant effect on trust, 4) Security of using digital payment methods (QRIS) has a significant effect on trust, 5) Trust has a significant effect on purchasing decisions, 6) Ease of use of digital payment methods (QRIS) has a significant effect on purchasing decisions, 7) The security of using digital payment methods (QRIS) has a significant effect on purchasing decisions.